Outdoor Advertising and the City: What was? What will be? Due to whatwill the heart calm down? - Bagina, Elena (project baikal, 2015)
The history of outdoor advertising extends back many thousands of years. At all times, the city environment included various kinds of advertising. In the XXth century, due to industrial and trade development, architectural objects and outdoor advertising objects came into sharp contradiction, which had grown into an open conflict by the end of the XXth century. In the West this process was faster than in Russia because of the peculiarities of social development of the latter. New techniques of outdoor advertising made this conflict sharper in the XXIst century. At the same time, the nature of architecture changed considerably. Buildings and constructions lost their cultural and historical implication. Fusion of architectural objects and outdoor advertising objects is observed everywhere. This trend will probably eliminate the existing conflict, though architecture will lose its historical roots and patrimonial features.
Keywords: city environment; outdoor advertising; architecture; conflict; regeneration of architecture; conflict resolution